THE EFFORT TO INCREASE STUDENT LEARNING MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION COURSES SURAH AL QOD AND AL-ALAQ THROUGH THE METHOD DISCUSSION IN CLASS VI UPTD. SDN NO. 213 HUTARIMBARU KECAMATAN KOTANOPAN KABUPATEN MANDAILING NATAL TAHUN PELAJARAN 2021/ - Mardiah Lubis (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This research was conducted at UPTD. State Elementary School No. 213 Hutarimbaru Kotanopan District, Mandailing Natal Regency with the research subjects being 21 Class VI students. From the results of classroom action research, there is an increase in students' learning outcomes of Islamic Religious Education through the application of the Learning Model Group discussion on the material of Surah Al-Qodr and Al-Alaq in Class VI UPTD. State Elementary School No. 213 Hutarimbaru Academic Year 2021/2022. This can be seen from student learning outcomes in the first cycle, the percentage of student learning mastery is 52.4% and the score of class completeness is 62.5% with the lowest score of 50 and the best score of 80. In the second cycle, the percentage of student learning completeness is 100% and the score is class completeness score of 85.2% with the lowest score of 70 and the best score of 90. This value has met the indicators of success. This means that there is an increase in student learning outcomes of Islamic Religious Education from cycle I to cycle II, for the percentage of student learning mastery there is an increase of 47.6% and the score of class completeness is 22.7%. The increase in Islamic religious education learning activities can also be seen from the results of observing student activities in the first cycle of 61.0%, while in the second cycle it is 73.2%. This means that there is an increase in student activity from cycle I to cycle II by 12.2%. Likewise with teacher performance, from the results of observations of teacher performance in the first cycle of 76%, while in the second cycle of 86%. This means that there is an increase in teacher performance from cycle I to cycle II by 10%. So that there is a significant influence between the Group Discussion Learning Model on Islamic Religious Education subjects on student learning outcomes in Class VI UPTD. State Elementary School No. 213 Hutarimbaru Academic Year 2021/2022 both in cycle I and in cycle II, meaning that the higher the student activity in student learning, the higher the value of learning outcomes obtained.